Comparison of ramal heights in individuals with clinically symmetrical and asymmetrical faces - Shahid, Rooma; Zaheer, Rumeesha; Jan, Abdullah; Mughal, Alaina Tariq; Shafique, Hafiza Zobia; Ghaffar, Fareena (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the mandibular ramal height differences between clinically symmetrical and asymmetrical face individuals. Method: The comparative cross-sectional study was conducted from May 2020 to July 2021 at the Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, and comprised subjects regardless of age and gender who were divided into two equal groups. Those with a clinically symmetrical face were in Group-I, and those with a clinically asymmetrical face were in Group-II. Mandibular ramal height of both sides of all subjects was measured, and asymmetry index. Differences of both right and left ramal heights of each group were measured and compared. Data was analysed using SPSS 26. Results: Of the 78 subjects, 40(51%) were males and 38(49%) were females. The overall mean age was 18±5.78 years, with 44(56%) aged 16-25 years, 28(36%) <15 years and 6(8%) >26 years. There was high but non-significant correlation between the right and left sides of both the groups (p>0.05). Inter-group differences were significant with respect to ramal height (p=0.000), whereas difference in terms of asymmetry index was not significant (p>0.05). Conclusion: There were significant differences in the mean ramal height between clinically symmetrical and asymmetrical face individuals. Key Words: Facial asymmetry, Mandibular condyle, Radiography, Panoramic.